2016
DOI: 10.1155/2016/8132741
|View full text |Cite
|
Sign up to set email alerts
|

A Histomorphological Pattern Analysis of Pulmonary Tuberculosis in Lung Autopsy and Surgically Resected Specimens

Abstract: Background. Tuberculosis (TB) is a major cause of morbidity and mortality globally. Many cases are diagnosed on autopsy and a subset of patients may require surgical intervention either due to the complication or sequelae of TB. Materials and Methods. 40 cases of resected lung specimens following surgery or autopsy in which a diagnosis of pulmonary tuberculosis was made were included. Histopathological pattern analysis of pulmonary tuberculosis along with associated nonneoplastic changes and identification of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 20 publications
1
13
0
2
Order By: Relevance
“…During the progression of TB, the infiltration of inflammatory mononuclear cells leads to the development of granulomas; a habitable niche for Mtb [69]. Furthermore, acute bronchopneumonia and necrotizing granulomas have been correlated with the pathology of pulmonary TB [70]. Remarkably, we observed a decrease in the Mtb burden and disease pathology of the lungs of the C6 administered group and augmented the potency of BCG (Fig.…”
Section: Discussionsupporting
confidence: 51%
“…During the progression of TB, the infiltration of inflammatory mononuclear cells leads to the development of granulomas; a habitable niche for Mtb [69]. Furthermore, acute bronchopneumonia and necrotizing granulomas have been correlated with the pathology of pulmonary TB [70]. Remarkably, we observed a decrease in the Mtb burden and disease pathology of the lungs of the C6 administered group and augmented the potency of BCG (Fig.…”
Section: Discussionsupporting
confidence: 51%
“…Gupta et al studied 40 cases diagnosed as pulmonary tuberculosis with a mean age was 41 years with a male preponderance (92.5%) which was not consistent with the present study. [16] A study was done by Meel et al on 200 cases which showed granulomas with carbon and silica particles in 1% males and 7% females. [17] These nontuberculous (dust reticulation) granulomas were not observed in the present study.…”
Section: Granulomatous Diseasesmentioning
confidence: 99%
“…In this situation, granulomatous lesions suggestive of TB can be found in up to 60% of cases [ 17 ]. Unfortunately, an important number of patients with miliary TB will not be diagnosed before a patient’s death, and it will be confirmed during autopsy [ 18 , 19 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%